A 71‐nucleotide deletion in the periaxin gene in an Italian patient with late‐onset slowly progressive demyelinating Charcot‐Marie‐Tooth disease. (15th September 2020) - Citrigno, L.; Zoccolella, S.; Lastella, P.; Simone, I. L.; Muglia, M.
Abstract : Background: Charcot‐Marie‐Tooth disease (CMT) constitutes a group of heterogeneous hereditary motor and sensor neuropathies. Mutations in the periaxin ( PRX ) gene cause CMT4F with an autosomal recessive early‐onset demyelinating neuropathy and are extremely rare in a non‐Romani white population. Methods: We report on a 66‐year‐old Italian man presenting with slowly progressive and late‐onset demyelinating CMT. The molecular analysis was performed using a custom panel containing 39 genes associated with the CMT phenotype. Results: The patient harbored a homozygous PRX 71‐nucleotide deletion (c.3286_3356del71, I1096fsX17). Conclusions: This is the first report that describes such a genetic mutation in a population of non‐Romani origin.